TAFSIR AD-DURR AL-MANTSUR FI TAFSIR AL-MA’TSUR KARYA IMAM AS-SUYUTHI (Studi Deskriptif Atas Metodologi Hingga Aspek Pendekatakan Interpretasi) - Ica Fauziah Husnaini (Mafatih, 2021)
Abstract Tafsir ad-Du>rr al-Mantsur fi Tafsir al-Ma’tsur by Imam Jalaluddin As-Suyuthi is part of the intertextuality of his previous work, the book Tarju>manul Qur’an. However in this study, the author only describes the main aspects in this interpretation, such as the methodology of interpretation, systematics of writing, patterns of interpretation and others. This type of research is literature research, using descriptive-analysis. The conclusion of this article explains that the background of writing the book Ad-Du>rr al-Mantsur fi Tafsir al-Ma’tsur is because - he (as-Suyuthi) wanted to make a summary of the Book of Tarju>manul Qur’an, so this interpretation was written. This interpretation is classified as the book of bi al-Ma'tsur, because generally the source of interpretation used is history, either using munasabah, history or hadith of the Prophet. friends, and tabi'in.